Neural Stem Cell-Conditioned Medium Ameliorated Cerebral Ischemia-Reperfusion Injury in Rats - HongNa Yang; Cuilan Wang; Hui Chen; Lan Li; Shuang Ma; Hao Wang; YaRu Fu; Tingyu Qu (Hindawi Limited, 2018)
Introduction. Our previous study suggested that NSC-CM (neural stem cell-conditioned medium) inhibited cell apoptosis in vitro. In addition, many studies have shown that neurotrophic factors and microparticles secreted into a conditioned medium by NSCs had neuroprotective effects. Thus, we hypothesized that NSC-CM had the capacity of protecting against cerebral I/R injury. Methods. Adult male Sprague-Dawley rats receiving middle cerebral artery occlusion surgery as an animal model of cerebral I/R injury were randomly assigned to two groups: the control group and NSC-CM-treated group. 1.5 ml NSC-CM or PBS (phosphate buffer saline) was administrated slowly by tail vein at 3 h, 24 h, and 48 h after ischemia onset. Results. NSC-CM significantly ameliorated neurological defects and reduced cerebral infarct volume, accompanied by preserved mitochondrial ultrastructure. In addition, we also found that NSC-CM significantly inhibited cell apoptosis in the ischemic hemisphere via improving the expression of Bcl-2 (B-cell lymphoma-2). Conclusion. NSC-CM might be an alternative and effective therapeutic intervention for ischemic stroke.